Faktor yang Berhubungan dengan ‎Intensi Pelaporan Capaian Indikator Mutu ‎pada Pengelola Data Mutu Unit Kerja Rumah Sakit Umum Daerah Raja Ahmad Tabib ‎Provinsi Kepulauan Riau Tahun 2022 - Lora Patal Tama; Retno Palupi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Reporting hospital quality indicators is an essential component of hospital quality improvement and patient safety programs. However, the reporting process at RSUD Raja Ahmad Tabib, Riau Islands Province, was not consistently implemented, indicating potential behavioral and organizational barriers among quality data managers. This study aimed to analyze factors associated with the intention to report hospital quality indicators based on the Theory of Planned Behavior among unit quality managers at RSUD Raja Ahmad Tabib in 2022. This quantitative study employed a cross-sectional design involving 135 validators and unit quality data collectors selected through total sampling based on inclusion criteria. Data were analyzed using univariate and bivariate analyses with the chi-square test. The findings demonstrated significant associations between attitude, subjective norms, and perceived behavioral control with the intention to report unit quality indicators. Positive attitudes, supportive subjective norms, and stronger perceived behavioral control increased the likelihood of strong reporting intentions among quality managers. The study highlights the importance of strengthening behavioral and organizational support systems to improve the implementation of hospital quality reporting and sustainable quality management practices.